2011
DOI: 10.1038/jp.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

The use of mobile robotic telemedicine technology in the neonatal intensive care unit

Abstract: Objective: To describe the use of a wireless, mobile, robotic telecommunications system in the Neonatal Intensive Care Unit (NICU).Study Design: In this prospective study utilizing 304 patient encounters on 46 preterm and term neonates in a level IIIa NICU, a bedside neonatologist ('on-site neonatologist'; ONSN) and a neonatologist at a distant location ('off-site neonatologist'; OFFSN) evaluated selected demographic information, laboratory data and clinical and radiological findings of the subjects. The OFFSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
1
58
0
2
Order By: Relevance
“…Although this study did not specifically address the validity of video assessment, evidence suggests that with the appropriate telemedicine technologies, high levels of agreement between bedside and remote physicians can be achieved on multiple physical examination findings, including genetic and neurologic examinations. 14,15 Because of the poor reliability and audiovideo quality of the technology used in this study, Mayo Clinic has transitioned the emergency telemedicine platform for newborn resuscitations to a wired solution. Local teams now use a wired telemedicine cart that is equipped with a high-definition camera with pan/tilt/zoom capabilities that can be remotely controlled by the neonatologist.…”
Section: Discussionmentioning
confidence: 98%
“…Although this study did not specifically address the validity of video assessment, evidence suggests that with the appropriate telemedicine technologies, high levels of agreement between bedside and remote physicians can be achieved on multiple physical examination findings, including genetic and neurologic examinations. 14,15 Because of the poor reliability and audiovideo quality of the technology used in this study, Mayo Clinic has transitioned the emergency telemedicine platform for newborn resuscitations to a wired solution. Local teams now use a wired telemedicine cart that is equipped with a high-definition camera with pan/tilt/zoom capabilities that can be remotely controlled by the neonatologist.…”
Section: Discussionmentioning
confidence: 98%
“…4,10,11 It has also been shown that telemedicine evaluation has good concordance with in-person evaluation of pediatric patients. 12,13 However, the effectiveness of telemedicine systems for pediatric critical care evaluation has not been thoroughly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 Additionally, the video screen is able to move as the physician or neonatal care specialist requires to care for patients. A digital stethoscope, otoscope, and pulse oximeter allow the physician to check vital signs, listen to heart and bowel sounds, and better evaluate the patient while in a remote location [15][16]. By working together with on-site nurses, off-site neonatal providers are able to maneuver the RTP machine on their own from a distant location, and motion sensors keep the machine from bumping into any incubators or medical equipment.…”
Section: Mobile Robotic Telemedicine In the Neonatal Intensive Care Unitmentioning
confidence: 99%
“…Robotic telepresence is a form of telemedicine that allows face-to-face contact between a specialist and a patient in a hospital [15][16]. An increase in preterm deliveries and an increase in survival rates with advances in neonatal medicine have resulted in a need for neonatal intensive care units (NICUs) to staff more neonatal specialists during more hours of the day [17].…”
Section: Mobile Robotic Telemedicine In the Neonatal Intensive Care Unitmentioning
confidence: 99%
See 1 more Smart Citation